Tetraethylammoniumacetate and tetraethylammonium bromide-based deep eutectic solvents as thermodynamic CO2 gas hydrate inhibitors - Sivabalan, V. (MDPI AG, 2020)
The thermodynamic gas hydrate suppression behavior of four Deep Eutectic Solvents (DESs) was evaluated in this paper. The mixtures of Hydrogen Bond Acceptors (HBA), Tetraethylammonium Acetate (TEAAC), and Tetraethylammonium Bromide (TEAB) with Hydrogen Bond Donors (HBD), Mono-Ethylene Glycol (MEG), and Glycerol were used to make the DES. The DESs were made at a 1:7 molar ratio for the combinations of TEAAGMEG, TEAAC:Glycerol, TEAB:MEG, and TEAB:Glycerol. The Hydrate Liquid-Vapor Equilibrium (HLVE) data for CO2 were evaluated through the T-cycle method at different temperature (273.15-283.15 K) and pressure (2-4 MPa) conditions in the presence and absence of 5 wt aqueous DES solutions. The inhibition effects showed by the DESs, including average suppression temperature (ÎT) and gas hydrate dissociation enthalpies (ÎHdjSS), were also calculated. The average suppression temperature values of the DESs ranged between 0.4 and 2.4, with the highest inhibition to lowest inhibition order being TEAB:Glycerol > TEAB:MEG > TEAAC:Glycerol > TEAAC:MEG. A comparison of the DES with conventional Thermodynamic Hydrate Inhibitors (THIs) showed that studied Deep Eutectic Solvents had better gas hydrate inhibition. The results proved that DES has the potential to be one of the promising alternatives in gas hydrate inhibition. Â© 2020 by the authors.